Assistance to industry in West Germany - Gerhard Fels (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1974)
This paper has four aims: First, it surveys the assistance given to individual sectors and industries in West Germany and makes an attempt to estimate its magnitude in terms of nominal and effective rates of protection; in contrast to the previous calculations the estimates presented here deal with protection in a wider context by including all measures of non-tariff assistance and by relating industrial protection to protection given to other parts of the economy. The second section of the paper discusses the objectives of assistance policy from a national and an international welfare point of view. The third section proceeds with a comparative analysis of the impact assistance measures have had on factor incomes and resource allocation among industries. Fourth and finally, some conclusions are drawn with respect to restructuring assistance policy.
Keywords: 330